Pengolahan Pakan Ternak Ruminansia melalui Penerapan Carrying Capacity di Desa Meurandeh Aceh Kota Langsa - Nurlina, Nurlina; Salman, Muhammad; Safrizal, Safrizal; Basriwijaya, Kiagus Muhammad Zain (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Langsa City is currently one of the centers for Aceh cattle cultivation. One of the areas or districts currently developing Aceh cattle farming is the Langsa Lama District, Langsa City. Carrying Capacity is a system that has been widely used by breeders. The use of this system is said to be very economical because it uses grass directly and uses little electricity. Carrying Capacity is highly recommended for small-scale farms because the system is economical and hygienic. The way Carrying Capacity works is the Incentive cage used to raise aceh cattle breeds. The direction of sunlight is modified so that the Aceh cattle become good seeds when they are productive. During the breeding process, the intensives in the cage are made as much as possible so that the daily body weight growth of the aceh cattle is fulfilled because it is triggered by feed that is highly nutritious and easily digested, the feed is given ad libitum and has been served in the form of chopped pieces using a grass chopper. small scale for 10-20 cows.